The Influence of Self-Regulated Learning on Learning Outcomes Moderated by The Flipped Classroom Model in Basic Mathematics Concept Lectures for Prospective Elementary School Teachers - Putri, Irni Rachmawati; Wuryandani, Wuri; Saptono, Bambang; Prananto, Irfan Wahyu (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
Self-regulated learning skills are very important for students to be able to plan, monitor, and evaluate learning independently so that they can achieve optimal academic abilities. Basic mathematical concepts are difficult to understand and require optimal learning readiness. Flipped classroom is a learning model that encourages students' SLR to achieve optimal learning outcomes. This study aimed to analyze the effect of SLR on learning outcomes moderated by flipped classrooms. The research uses a quantitative approach by applying linear regression and moderation regression data analysis techniques. The subjects of this study were 38 people, 7 of whom were male students and 31 female students, with each subject in the age range of 16-18 years, who acted as class D PGSD students, Yogyakarta State University, Class of 2024. The results showed that the effect of SLR on the learning outcomes of PGSD students in introductory mathematics concept lectures was only 1.2%. However, suppose SLR is applied to the practice of flipped classroom learning. In that case, it can moderate the effect of the SLR variable on the learning outcomes of basic mathematics concepts of number concepts by up to 43.3%. This concludes that the SLR of students will significantly affect the existence of learning practices designed with the flipped classroom model. Thus, implementing the flipped classroom substantially moderates the effect of SLR on the learning outcomes of elementary school teacher candidates in introductory mathematics concept lectures. Keywords: Self-regulated Learning, Learning Outcomes, Flipped Classroom